How motivations for esports consumption influence the esports sponsorship response: the favourability, brand awareness and purchase intention effects - Fernandes, António Jorge Alvoeiro (2019)
Esports is an emerging sport that is growing exponentially in popularity in the past years. The fact that it is played online, mainly transmitted through web streaming and its inherent international nature, being for the big tournaments which involve teams of every continent, or the players that compose those teams which are from many different countries, creates a new path to be explored for many brands that want to engage in the sponsorship deals. It also creates a new landscape of study for which are the motivations for people to spectate this sport taking into account the differences from the traditional ones. Thus, this dissertation gives an overall analysis of what are esports and its stakeholders and the sponsorship traits especially on the sports environment. In order to create a new framework, the basis of the study was on the motivations for watching traditional sports which are Vicarious Achievement, Acquiring Knowledge, Aesthetics, Drama, Escapism, Physical Attractiveness, Physical Skills of the Athletes, Social Interaction, Novelty and Enjoyment of Aggression and the sponsorship response traits such as favorability, awareness and purchase intention. The data collection was done by means of a quantitative analysis through a questionnaire based on the Motivation Scale for Sports Consumption and the Determinants of Sports Sponsorship Response. The results allow us to assess which are the motivations that were positively influencing the consumption and mainly to conclude that some of the reasons for watching esports influence the response to sponsorship.